Gilbert & George : in Moscow - Farson, Daniel (London : Bloomsbury Publishing Ltd., 1991)
In the Spring of 1990, Daniel Farson flew to Moscow with Gilbert & George. He was there to cover their exhibition for the Sunday Telegraph, but the experience became so strange that he came downstairs one morning in the Ukraine Hotel and told them - This should be a book. Apart from the problems of staging such a show in Russia - the catalogues weighed 7 1/2 tons alone - they arrived at a crucial time in Moscow's history. Despite a sense of impending doom there was a momentary mood of optimism, a fleeting freedom reflected in the speech by a Soviet spokesman who admitted that such an event would not have been allowed in the previous years of Stagnation. It was not by change that Gilbert & George chose One World as the exhibition's title, for their work is noted for crossing barriers, appealing to all people - especially the young Judging by the enthusiasm of the young Russians who crowded into the rooms on opening day, their claim that this was a Turning Point In 20th Century Art was confirmed. Yet Gilbert & George, probely the most controversial artists working in the world today, have been subjected to such virulent abuse that it verges on paranoia. The Mosow exhibition received no official blessing or funding. Farson asks Why The Hatred ? and Who Are Gilbert & George ? Approaching them with an open mind he presents the case both for and against them. His gradual understanding of the artists and their work runs parallel with the historic events in Moscow, reaching its climax as Farson was swept into the May Day demonstration in Red Square. The book is richly illustrated with black and white photographs and colour plates.
Engels
With Gilbert & George in Moscow, Bloomsbury, London
boek
Keywords: Gilbert & George; Moscow